Designing Dexter-based Cooperative Hypermedia Systems - Grønbæk, Kaj; Hem, Jens A.; Madsen, Ole Lehrmann; Sloth, Lennert (DAIMI Report Series, 1993)
This paper discusses issues for the design of a Dexter-based cooperative hypermedia architecture and a specific system, DeVise Hypermedia (DHM), developed from this architecture. The Dexter Hypertext Reference Model was used as basis for designing the architecture. The Dexter model provides a general and solid foundation for designing a general hypermedia architecture. It introduces central concepts and proposes a layering of the architecture. However, to handle cooperative work aspects, such as sharing material and cooperative authoring, we have to go beyond the Dexter model concepts. To deal with such aspects we have extended our implementation of the Dexter concepts with support for long-term transactions, locking and event notification as called for by Halasz. The result is a platform independent architecture for developing cooperative hypermedia systems. The architecture consists of a portable kernel that constitutes an object oriented framework for developing Dexter compliant hypermedia systems. It is a client/server architecture including an object oriented database (OODB) to store the objects implementing the Dexter Storage Layer. We use a general OODB being co-developed to support long term transactions, flexible locking, and event notification. The transaction and locking mechanism support several modes of cooperation on shared hypermedia materials, and the notification mechanism supports the users in maintaining awareness of each others' activity. The portable kernel was used to implement the DHM system on two quite different platforms: UNIX/X-windows and Apple Macintosh.